CatRAPID omics v2.0: going deeper and wider in the prediction of protein–RNA interactions. Issue Volume 49:Issue W1(2021) (4th June 2021) - Armaos, Alexandros; Colantoni, Alessio; Proietti, Gabriele; Rupert, Jakob; Tartaglia, Gian Gaetano
Abstract: Prediction of protein–RNA interactions is important to understand post-transcriptional events taking place in the cell. Here we introduce cat RAPID omics v2.0, an update of our web server dedicated to the computation of protein–RNA interaction propensities at the transcriptome- and RNA-binding proteome-level in 8 model organisms. The server accepts multiple input protein or RNA sequences and computes their cat RAPID interaction scores on updated precompiled libraries. Additionally, it is now possible to predict the interactions between a custom protein set and a custom RNA set. Considerable effort has been put into the generation of a new database of RNA-binding motifs that are searched within the predicted RNA targets of proteins. In this update, the sequence fragmentation scheme of the cat RAPID fragment module has been included, which allows the server to handle long linear RNAs and to analyse circular RNAs. For the top-scoring protein–RNA pairs, the web server shows the predicted binding sites in both protein and RNA sequences and reports whether the predicted interactions are conserved in orthologous protein–RNA pairs. The cat RAPID omics v2.0 web server is a powerful tool for the characterization and classification of RNA-protein interactions and is freely available at http://service.tartaglialab.com/page/catrapid_omics2_group along with documentation and tutorial. Graphical Abstract: